Realities of Microenterprises’ ICT Use for Business Activities and for Acquiring Online Government Support: A Study in Western Cape Province, South Africa - Osman, Muhammad Ameer; Malanga, Donald Flywell; Chigona, Wallace (My University, 2019)
This article provides findings from a study, in South Africa’s Western Cape Province, of microenterprises’ experiences and perceptions of use of information and communication technologies (ICTs) for general business activities and for acquiring online government business support information. Using the capability approach (CA) theoretical framework, the study analysed data from interviews with microenterprise owners and digital government experts. The study found that the microenterprises were adept in their use of ICTs in their businesses, but that they encountered problems in using online government business support information services. These problems were found to be the result of deficiencies in the online services’ content, structure, design, navigation, mobile-friendliness, language usage and bureaucratic requirements.